Influence of high pressure processing on qualities of celery-based juices during refrigerated storage - Le, Uyen Ngoc Phuong; Ratphitagsanti, Wannasawat; Therdthai, Nantawan (Agriculture and Natural Resources, 2023)
Importance of the work: As a rich source of nutrients, celery has been widely chosen as a food or beverage item. However, a short shelf life is the main concern in celery juice production. Objectives: To investigate the combination of natural juice acidification and high pressure processing (HPP) to enhance microbial and enzyme inactivation, including shelf life extension of celery-based juice. Materials & Methods: Lime and apple juices were used to mix with celery juice as natural acidifiers to adjust the juice pH. Three juice formulations—celery, celery-lime and celery-apple—were prepared and treated at 400, 500 or 600 MPa for 5 min. Juice qualities were investigated during 8 wk of storage in refrigerated conditions. Results: The addition of fruit juice led to differences in the properties of the celery-based juices. Celery-lime juice provided greater inactivation of microorganisms and enzymes than the other two formulations. The highest pressure maintained the levels of important physical properties, total phenolic compounds and antioxidant capacity of juices. Throughout storage, the aerobic count remained under 2 log colony forming units/mL with no detection of yeasts and molds. Residual activity of polyphenoloxidase and peroxidase was reduced to under 36% and 50% in the celery-lime juice and celery-juice, respectively. The antioxidant capacity was maintained at more than 50%, indicating that HPP at 600 MPa was the most suitable condition. Main finding: HPP showed potential as an alternative preservation method for celery-based juices for up to 8 wk of storage. Furthermore, the combination of HPP and acidifier from low-pH fruits could provide an option for vegetable juice production with greater nutritional value and safety assurance.